Implementasi Manajemen Pendidikan Islam di Pesantren - Indarsih, Fajar (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Educational management is the process of applying management principles and theories in managing activities in formal educational institutions to streamline the achievement of educational goals. The nuances of Islamic boarding schools which are arguably backward and difficult to open new breakthroughs as a renewal of the education system must be forced to make changes by incorporating Islamic Education Management. Application of management in the management of education in Islamic boarding schools, madrasah, universities must be supported by personnel resources and other resources that are used to realize the performance of high education organizations in order to achieve reliable quality graduates, mobilize these personnel there are elements of motivation, directing and leading them cooperate well and harmoniously. It must all be done in order to answer the challenges of the times like today. Islamic education management will not lose its function in humanizing humans because management of Islamic education is the most important part of managing education in introducing humans to worldly and religious values.